Environmental changes across the Jurassic-Cretaceous boundary in the western proto-Gulf of Mexico: chemo- and biostratigraphic correlation of NE Mexican sections - Hennhöfer, Dominik K.; Zell, Patrick; Stinnesbeck, Wolfgang (Palaeogeography, palaeoclimatology, palaeoecology, 2021)
Late Jurassic-earliest Cretaceous (Kimmeridgian-earliest Berriasian) marine shelf sediments in northeastern Mexico reveal repeated temperature-related oceanic and biotic turnovers in the northwestern proto-Gulf of Mexico. Our detailed geochemical analysis of four sections crossing the Jurassic-Cretaceous (J/K) boundary is based on chemostratigraphic correlation and repeated mollusk assemblage changes reflecting significant environmental fluctuations, including sea level and marine redox conditions. The present study confirms tectonic tilting and rapid drowning of shallow-water environments in the early Kimmeridgian, associated with the near-synchronous spread of bottom-water anoxia in shelf areas bordering the proto-Gulf of Mexico. Boreal cold-water faunal elements are associated with a sea-level drop in the late Kimmeridgian, while a transient transgressive-regressive phase is interpreted for the shelf transect in the earliest Tithonian. A general transgressional trend is reported for the Tithonian and across the J/K boundary, while the migration into the area of boreal and austral high-latitude faunal elements marks specific intervals. We hypothesize that oscillations in the oceanic current system were responsible for the intermittent establishment of cold-water boreal and austral faunal assemblages in the northwestern proto-Gulf of Mexico.
Gesehen am 03.03.2022